Scaffolding argumentative writing through Reading to Learn (RtL) pedagogy: a case study of three grade 11 English second language teachers in Namibia - Matengu, Ernest Samubu (Rhodes University, Faculty of Education, Department of Education)
The central aim of this study was to investigate the positive impact of Reading to Learn (RtL) pedagogy in enhancing Grade 11 learners' argumentative writing skills. This was a case study of one school in Otjozondjupa region in Namibia. The pedagogy, RtL, was designed to address learning inequalities with marginalised communities in Australia. Coupled with challenges in literacy development in learners, current methods have not successfully addressed the teaching and learning of argumentative writing amidst learning inequalities. This study employed the six stages of Scaffolding Interaction Cycle of RtL in order to teach argumentative writing. As is evidenced in recent research, the scaffolding cycle of RtL provides equal opportunities to learners from diverse backgrounds to attain epistemological access at the same pace. RtL's theoretical and conceptual framework is derived from Bernstein's theory of education as pedagogic discourse (a device for maintaining inequality in society), Vygotsky's theory of learning as a social process and Halliday's model of language as text in social context. The two research questions for this study were: (1) What role does Reading to Learn (RtL) pedagogy play in developing Grade 11 learners' ability to write argumentative essays? And (2) How can the implementation of RtL pedagogy through scaffolding impact on/improve learners' literacy skills development for argumentative essay writing? This qualitative case study generated data through observation of three teachers' lessons, a Stimulated Recall Interview (SRI) conducted with the three teachers and learners' pre and posttest of argumentative essays. The findings of this study revealed that teachers found RtL as a comprehensive pedagogy that makes teaching and learning of argumentative writing successful through systematic scaffolding of learning. Learners' written pre and posttest also showed a narrowing of the gap between weak and strong learners in that weak learners recorded an upward trend similar to that of strong learners in their posttest. Given the design of RtL and studies conducted globally, the findings of this study can be comparable.
Keywords: Rose, David, 1955-; Reading (Secondary); Persuasion (Rhetoric)-- Study and teaching (Secondary)-- Namibia; English language Writing-- Study and teaching (Secondary)-- Namibia; English language Rhetoric-- Study and teaching (Secondary)-- Namibia; English language-- Study and teaching (Secondary) Foreign speakers Case studies; Reading to Learn; Scaffolding Interaction Cycle